Impact Of Multiple Positions And Organizational Culture On Job Performance At Asca Elpida Service Bureu - Maretasari, Rina; Mukhlis, Imam (UMSurabaya Publishing, 2025)
The psychology bureau is a place for the public to tell a problem to the experts or psychological tests for job recruitment, psychological tests for students, and other IQ tests. AscaElpida Service Bureau is an institution engaged in services. Based on this, the research aims to find out the effect of dual positions and work culture on work performance at the AscaElpida service bureau. The research method used is qualitative. Data will be collected using interviews, observation, and documentation with as many as 2 informants. The study results indicate that job performance at the AscaElpida Service Bureau is the target that has been achieved. The number of customers increased, and there are multiple positions, namely leaders who carry out more than one activity and are carried out with one person. The organizational culture applied to the Asca Elpida Service Bureau is not optimal enough. This makes employees less efficient or can hinder work. Concurrent positions and organizational culture should be controlled and given maximally so that employees can pay more attention to performance for better performance.